"Granito e arcobaleno". Forme e modi della scrittura auto/biografica - Antonielli, Arianna; PALLOTTI O BALLOTTI, Donatella (Biblioteca di Studi di Filologia Moderna, 2019)
Granito e arcobaleno. Forme e modi della scrittura auto/biografica collects essays on issues regarding relationships and their fragile balances, between reality and fiction, experience and memory, private and public, autonomy and relatedness, referential truth and subjective truth, between the self and the other. The contributions also involve concepts such as the social, cultural, geopolitical or even rhetorical space, where the auto/biographical subject is situated; the 'materiality' of the body, which perceives and internalizes the images, sensations and experiences of the external world; the agency and the linguistic, discursive, social and cultural constraints to which it is subjected. After a theoretical introduction, this volume explores individual case studies that can be traced back to different and sometimes distant cultural realities, then concludes with an artist's reflection on art and life.